A Combinatorial Virtual Screening Approach Driving the Synthesis of 2, 4‐Thiazolidinedione‐Based Molecules as New Dual mPGES‐1/5‐LO Inhibitors. (17th February 2020) - Lauro, Gianluigi; Terracciano, Stefania; Cantone, Vincenza; Ruggiero, Dafne; Fischer, Katrin; Pace, Simona; Werz, Oliver; Bruno, Ines; Bifulco, Giuseppe
Abstract: Dual inhibition of microsomal prostaglandin E2 synthase‐1 (mPGES‐1) and 5‐lipoxygenase (5‐LO), two key enzymes involved in pro‐inflammatory eicosanoid biosynthesis, represents a new strategy for treating inflammatory disorders. Herein we report the discovery of 2, 4‐thiazolidinedione‐based mPGES‐1/5‐LO dual inhibitors following a multidisciplinary protocol, involving virtual combinatorial screening, chemical synthesis, and validation of the biological activities for the selected compounds. Following the multicomponent‐based chemical route for the decoration of the 2, 4‐thiazolidinedione core, a large library of virtual compounds was built (∼2.0×10 4 items) and submitted to virtual screening. Nine selected molecules were synthesized and biologically evaluated, disclosing among them four compounds able to reduce the activity of both enzymes in the mid‐ and low‐ micromolar range of activities. These results are of interest for further expanding the chemical diversity around the 2, 4‐thiazolidinedione central core, facilitating the identification of novel anti‐inflammatory agents endowed with a promising and safer pharmacological profile. Abstract : Solid workflow : 2, 4‐Thiazolidinedione‐based mPGES‐1 inhibitors were identified by applying a multidisciplinary protocol involving virtual combinatorial screening, chemical synthesis, and biological evaluation of the selected compounds. These compounds were also found to inhibit 5‐LO, another key enzyme involved in the arachidonic acid cascade for leukotriene biosynthesis. These results highlight the applicability of this workflow for the discovery of pharmacologically relevant compounds.